2008
DOI: 10.1186/1476-5918-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with metabolic syndrome have a history of low aerobic fitness and physical activity levels

Abstract: Purpose: Metabolic syndrome (MS) is a clustering of cardiovascular disease risk factors that identifies individuals with the highest risk for heart disease. Two factors that may influence the MS are physical activity and aerobic fitness. This study determined if adolescent with the MS had low levels of aerobic fitness and physical activity as children.Methods: This longitudinal, exploratory study had 389 participants: 51% girls, 84% Caucasian, 12% African American, 1% Hispanic, and 3% other races, from the Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 36 publications
(51 reference statements)
6
97
0
4
Order By: Relevance
“…Those with CMS had an adjusted Relative Risk (RR) of 1.46 for developing mobility limitations. The risk increased with higher central obesity and worse hyperglycemia [74,75].…”
Section: Lack Of Exercisementioning
confidence: 99%
“…Those with CMS had an adjusted Relative Risk (RR) of 1.46 for developing mobility limitations. The risk increased with higher central obesity and worse hyperglycemia [74,75].…”
Section: Lack Of Exercisementioning
confidence: 99%
“…In particular, six studies using objective measures of PA (that is, accelerometer) have found in healthy children an inverse relationship between PA level and metabolic risk factors, independent of age, gender and body mass index (BMI) or adiposity. [57][58][59][60][61][62] Overall, in overweight children a high fitness level was associated with a risk for MS similar to that of normal-weight children with a low fitness level, thus vanishing differences between body weight classes 21,50,[63][64][65] and contributing to long-term prevention. 66 The preventive role of PA in children was shown in a large study where a dose-response relationship between PA and blood pressure was found, and PA showed a strong effect on blood pressure when predicting hypertensive values.…”
Section: Physiopathological Basis Of the Msmentioning
confidence: 99%
“…In a longitudinal study by McMurray et al (53) , children with MetS (4?6 %) had lower PA levels and CRF outcomes than the non-MetS group. Some 4?25 % of prepubertal children in the current study presented MetS; these children belonged to the LCF group and did not perform PA. A similar percentage has been reported in another study of children (1) .…”
Section: Discussionmentioning
confidence: 94%